Nutritional Status And Health Profile Among Single Mothers In Kota Bharu, Kelantan - Sakinah, Harith; Noor Aini, Mohd Yusoff (2018)
The objective of this cross-sectional study is to determine the nutritional status and health profile of single mothers in Kota Bharu, Kelantan. A total of 100 single mothers aged 18-59 years old were involved in this study. Assessment of blood glucose, blood pressure, height and weight and food consumption were done to each respondent. Results showed that the random blood glucose level of 82.0% single mothers was normal (within 4.4-8.0mmol/L), 18.0% exceeded 8.0mmol/L although only 10.0% of them were diagnosed with diabetes based on clinical history. Meanwhile, 46.0% had normal blood pressure level. The result showed that 33.0% of the subjects have normal BMI, 6.0% of them fall in the category of underweight, 39.0% were overweight and 22.0% were obese. It is suggested that future intervention programs should focus on preventing obesity problems related to chronic diseases.